Q. 103.7( 3 Votes )

# Verify whether the following are true or false:

(i) –3 is a zero of x – 3

(ii) is a zero of 3x + 1

(iii) is a zero of 4 –5y

(iv) 0 and 2 are the zeroes of t^{2} – 2t

(v) –3 is a zero of y^{2} + y – 6

Answer :

(i) –3 is a zero of x – 3

False because zero of x – 3 = 3 ∵ x – 3 = 0 ⇒ x=3

(ii) is a zero of 3x + 1

True because zero of 3x + 1 = – 1/3 ∵ 3x + 1 = 0 ⇒ x = – 1/3

(iii) is a zero of 4 –5y

False because zero of 4 – 5y is 4/5 ∵ 4 – 5y =0 ⇒ – 5y = – 4 ⇒ y = 4/5

(iv) 0 and 2 are the zeroes of t^{2} – 2t

T^{2} – 2t = t(t – 2) = 0 ⇒ t = 0 or 2

Hence the zero of the polynomial are 0 and 2 . the given statement is true.

(v) –3 is a zero of y^{2} + y – 6

y^{2} + y – 6 = 0

⇒ y^{2} + 3x – 2x – 6 = 0

⇒ y (y + 3) – 2(x + 3) = 0

⇒ (y – 2) (y + 3) =0

⇒ y = 2 or – 3

Hence – 3 is one of the zero of the polynomial. The given statement is true.

Rate this question :

The zeroes of the polynomial p (x) = x^{2} + x - 6 are

Zero of the polynomial p(x) = 2x + 3 is

RS Aggarwal & V Aggarwal - MathematicsIf find

(i) f (0)

(ii) f (4)

(iii) f (-5)

RS Aggarwal & V Aggarwal - MathematicsIf 2 and -1/3 are the zeros of the polynomial 3x^{3} - 2x^{2} - 7x - 2 find the third zero of the polynomial.

If (x + 1) is a factor of 2x^{2}+ kx, then k =?

If (x^{2}+ kx – 3) = (x – 3 ) (x + 1) then k =?

The zeroes of the polynomial p (x) = x^{2} – 3x are

The zeroes of the polynomial p (x) = 3x^{2} – 1 are

If p(x) = x^{3} + x^{2} + ax + 115 is exactly divisible by (x + 5) then a = ?